Robot-assisted transcranial magnetic stimulation using hybrid position/force control. (16th December 2020) - Jaroonsorn, Prakarn; Neranon, Paramin; Smithmaitrie, Pruittikorn; Dechwayukul, Charoenyutr
Abstract : Transcranial magnetic stimulation is a powerful and non-invasive technique to stimulate nerve cells in the brain to improve symptoms of depression. It needs accurate contact force and positioning of a stimulating coil to offer effective treatment. Conventionally, a neurologist has to manually place the coil on the patient's head at a predefined position and orientation throughout the 30-to-45-minute treatment. This paper consequently highlights the design of a robot control framework used for the transcranial magnetic stimulation. The hybrid Proportional-Derivative position and Proportional–Integral force control scheme was successfully implemented on the effective robotic system. The system can track the head movement by using the Kinect camera and simultaneously maintain the contact force between the magnetic coil and the head in real-time. The optimal gain tuning technique was adopted. It delivered PD gains of K p  = 75.0, K d =2.0 and PI gains of K p  = 0.09 and K i  = 0.011, respectively. This provides a faster response of the robot end-effector with a small interactive force error. The experimental results show that when the head has translational and rotational motions, the robot-assisted transcranial magnetic stimulation control system performs with a safe and reliable manner validated by the quantitative measurement. GRAPHICAL ABSTRACT: UF0001